PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP RENTABILITAS PADA PT. BANK NAGARI PERIODE 2015-2020 - Fela Nuansa Putri; Sophan Sophian (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
The purpose of this study was to analyze the effect of liquidity and solvency on profitability at PT. Bank Nagari. This type of research is quantitative, where this study uses time series data (time period). The data taken in this research are 60 monthly financial report data of Pt.Bank Nagari. The data collection technique used in this research is documentation/library study. The type of data used in this study is quantitative data, while the data source is secondary data. The data analysis technique uses multiple linear regression with the help of the Eviews 12 program. The hypothesis is tested using t-test at = 0.05. The results of this study indicate that liquidity has an effect negative and significant to profitability, while solvency has no effect on profitability. The coefficient of determination of liquidity and solvency is 29.72% while the remaining 70.28% is explained in other variables.